Early Maturation of Corpus Luteum in Rabbits - Effect of Sildenafil Citrate on Luteolytic Capacity in the Early Luteal Period - Ucar, Eyyup Hakan; Peker, Cevdet; Erdogan, Gunes; Kose, Mehmet; Atli, Mehmet Osman (Acta Scientiae Veterinariae, 2023)
Background: Prostaglandin F2 alpha (PGF2α) binds to the specific receptor (PTGFR) on the corpus luteum (CL) in mammals, inducing regression of the CL structure (luteolysis) and initiating a new cycle. While PGF2α is effective only on mature CL, the immature CL structure (early luteal phase) resists PGF2α. In this study, sildenafil citrate, which is used to increase blood flow in the genital organs for treating specific pregnancy issues in women, was administered during the early luteal phase in a rabbit model to test the hypothesis of enhancing blood flow to the CL, thereby promoting earlier maturation and enabling a response to PGF2α. Materials, Methods & Results: The study was conducted in 2 sub-studies: clinical and molecular. A large number of rabbits were initially included in the sub-studies to ensure a sufficient number of pseudo-pregnant rabbits. Ovulation in rabbits was induced with buserelin acetate and was considered as day 0 of the study. The sub-studies were continued with rabbits whose pseudo-pregnancies were confirmed according to progesterone (P4) results. As a result, the studies were continued with a total of 41 pseudo-pregnant New Zealand female rabbits, 21 of which were included in the clinical sub-study and 20 in the molecular sub-study. In both sub-studies, on day 3 of the luteal period, rabbits in the treatment group received 5 mg/kg sildenafil citrate and all rabbits received a single dose of exogenous PGF2α on day 4 to induce luteolysis. In the clinical sub-study, echotexture and intraovarian blood flow changes in the ovaries were determined by ultrasonography (USG) examination. In the molecular sub-study, the expression changes of Hypoxia Inducible Factor 1 Alpha (HIF1A) and Vascular Endothelial Growth Factor (VEGF) related to angiogenesis, Steroidogenic Acute Regulatory Protein (StAR) related to P4 metabolism, Prostaglandin-Endoperoxide Synthase 2 (PTGS2) related to prostaglandin (PG) mechanism and 15-Hydroxyprostaglandin Dehydrogenase (HPGD) genes at mRNA level were determined using Real Time Polymerase Chain Reaction (RT-PCR) in CL tissues obtained with ovariohysterectomy (OVH) at 1 and 12 h after PGF2α injection. In addition, blood samples were collected for determine P4 levels from all rabbits. In the clinical sub-study; there was no difference between the groups in mean gray values (MGV), whereas there was a significant decrease in both pulsatile index (PI) and resistance index (RI) values at 40 min after PGF2α injection (P < 0.05). In the molecular sub-study, it was determined that sildenafil citrate had no significant effect (P > 0.05) on the expression levels 1 and 12 h after PGF2α injection. According to the results of the molecular sub-study, no significant effect of sildenafil citrate on the mRNA expression levels in the investigated genes was detected (P > 0.05). However, within each group, differences were found according to OVH time after PGF2α injection. It was observed that PTGS2 and HPGD mRNA expressions decreased at the 12th h compared to the 1st h, while HIF1A expression increased (P < 0.05). Discussion: According to the results obtained from clinical and molecular sub-studies, it was determined that a single dose of sildenafil citrate (5 mg/kg) applied on the 3rd day of the luteal period did not contribute to the maturation process of the CL, did not increase blood flow, and was insufficient to break the resistance of the CL against PGF2α applied on the 4th day of the luteal period. However, a significant decrease in the PI value at the 40th min after PGF2α injection suggests that sildenafil citrate has a supportive effect, and that this decrease is also seen in the RI value, suggesting that its effect is insufficient against the vasoconstrictive effect of PGF2α. Keywords: sildenafil citrate, PGF2 alpha, corpus luteum, early luteal stage, rabbit.